Fall Tailoring Interventions for Patient Safety Brazil Program: an evaluability study in a teaching hospital - Adeli Regina Prizybicien de Medeiros; Luciana Schleder Gonçalves (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to present the theoretical model, logic model, and the analysis and judgment matrix of the Fall TIPS Brazil Program. Methods: a qualitative, participatory research approach, in the form of an evaluability study, encompassing the phases (1) problem analysis; (2) program design, development, and adaptation to the Brazilian context; (3) program dissemination. Data were collected through document analysis and workshops. Results: through document analysis, workshops with stakeholders from the participating institution, and validation with key informants, it was possible to identify the program's objectives, expected outcomes, and the target audience. This allowed the construction of theoretical and logic models and, through evaluative questions, the identification of indicators for the evaluation of the Fall TIPS Brazil Program. Final Considerations: this study has provided insights into the Fall TIPS program, the topic of hospital fall prevention, and the proposed models and indicators can be employed in the implementation and future evaluative processes of the program.